Effect of subcritical water flash release processing on buckwheat flour properties. (6th January 2023) - Plumier, Benjamin; Kenar, James A.; Felker, Frederick C.; Winkler‐Moser, Jill; Singh, Mukti; Byars, Jeffrey A.; Liu, Sean X.
Abstract: Background: Buckwheat ( Fagopyrum esculentum ) is rich in bioactive components. However, many of these components are trapped within cellular structures, making them inaccessible. Buckwheat flour was hydrothermally modified using subcritical water coupled with a flash pressure release (SCWF). The effects of the SCWF parameters (120, 140, and 160 °C and hold times of 0, 15, and 30 min) on the flour's structure, physicochemical, and functional properties were studied relative to the raw flour. Results: Treatment deepened the flour color with increasing processing temperatures and hold times. Starch content remained unchanged though its granular structure was disrupted. SCWF treatments lowered total phenolic content compared with the raw flour, except for 160 °C–30 min, where total phenolic content increased by 12.7%. The corresponding antioxidant activities were found consistent with phenolic content. Soluble and insoluble dietary fiber amounts were not substantially influenced at 120 and 140 °C, whereas treatments at 160 °C (15 and 30 min hold) decreased soluble dietary fiber while increasing insoluble dietary fiber. Protein content increased 70–109% in some treatments, suggesting greater protein accessibility. Water‐holding capacity significantly increased for flour treated at 120 °C, whereas only slight improvements occurred at 140 and 160 °C. Conclusions: Subcritical water flash processing can modify the compositional and functional properties of buckwheat flour depending on the choice of reaction conditions. Observed changes were consistent with alteration of the flour's cellular structure and allow some components to become more accessible. The resulting SCWF‐modified buckwheat flours provide new food ingredients for potential use in ready‐to‐eat foods and spreads with improved health benefits. Published 2022. This article is a U.S. Government work and is in the public domain in the USA.